Stakeholders' Perceptions of Aquaculture and Implications for Its Future: A Comparison of the U.S.A. and Norway - Chu, Jingjie (2012)
Aquaculture is a controversial issue in the U.S.A., and to what extent U.S. aquaculture stakeholders support its expansion determines the future of this industry. This paper compares the perceptional differences of aquaculture stakeholders in the U.S.A. and Norway, and investigates how their perceptions influence their decisions to support aquaculture development. Original data were collected from an online survey of key aquaculture stakeholders and experts in both countries. Based on multinomial logit models, all of the perception variables contribute significantly to the likelihood that an aquaculture stakeholder is willing to support aquaculture expansion. These findings provide useful information for U.S. and Norwegian aquaculture policymakers, regulators, and stakeholders regarding how perceptions influence decisions; the key perceptional differences between the U.S.A. and Norway; and how policies, practices, and education could change perceptions of aquaculture stakeholders and thereby the future of U.S. and Norwegian aquaculture.